2015
DOI: 10.1038/ki.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Lipid imaging within the normal rat kidney using silver nanoparticles by matrix-assisted laser desorption/ionization mass spectrometry

Abstract: The well-characterized cellular and structural components of the kidney show distinct regional compositions and distribution of lipids. In order to more fully analyze the renal lipidome we developed a matrix-assisted laser desorption/ionization mass spectrometry approach for imaging that may be used to pinpoint sites of changes from normal in pathological conditions. This was accomplished by implanting sagittal cryostat rat kidney sections with a stable, quantifiable and reproducible uniform layer of silver us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 31 publications
0
65
0
Order By: Relevance
“…Additionally, cholesterol adducted with three silver atoms and cholesteryl esters (CE) plus one silver atom were observed as minor peaks. The assignment of M+Ag 3 for cholesterol has been discussed in an earlier study [6]. The major peak for cholesterol is a plusone silver atom adduct.…”
Section: Assignment Of Lipid Species Detected By Agnps In Rat Brainmentioning
confidence: 90%
See 2 more Smart Citations
“…Additionally, cholesterol adducted with three silver atoms and cholesteryl esters (CE) plus one silver atom were observed as minor peaks. The assignment of M+Ag 3 for cholesterol has been discussed in an earlier study [6]. The major peak for cholesterol is a plusone silver atom adduct.…”
Section: Assignment Of Lipid Species Detected By Agnps In Rat Brainmentioning
confidence: 90%
“…A few of the most abundant PCs were observed as +Ag and +K adducts. However, despite the high abundance of PCs in brain tissue, these mass peaks were very low in intensity due to nanoparticle matrices preference for ionizing more neutral lipids [5,6,23].…”
Section: Assignment Of Lipid Species Detected By Agnps In Rat Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, an automated registration procedure can be performed, 145 which ultimately facilitates the correlation to anatomical atlases. Besides the identification, the number of detected metabolites is important, which can be increased by carrying out the MALDI MSI analysis in both, positive and negative ionisation mode, using certain matrices (1,5-diaminonaphthalene, 84 quercetin, 86 dithranol, 88 silver nanoparticles 164 or the combination of two (cyano-4-hydoxycinnamic acid and 9-aminoacrdine). 147 Besides, cancer applications, various other diseases, such as infections of hepatitis B virus, 81 atherosclerosis, 148 fabry, 79 peridontal, 149 alzheimer's, [150][151][152] epilepsia, 153 stroke, 154 schizophrenia, 155 and stargardt disease 82 have been investigated to shade light into the underlying disease mechanism.…”
Section: Metabolomicsmentioning
confidence: 99%
“…Recently, a surface‐assisted laser desorption/ionization (SALDI)‐IMS method using Ag nanoparticles was shown to allow the detection of DAG in the kidney. Na and K, 107 Ag, 109 Ag adduct ions, and fragment ions were obtained slightly, although Ag nanoparticles (AgNPs) were proven to be an effective matrix for the analysis of DAG containing double bonds . In the study, authors reported that ultaviolet absorption wavelength of AgNPs caused the low efficiencies of desorption and ionization.…”
Section: Introductionmentioning
confidence: 99%